Analisis Kedisiplinan Waktu Kerja Karyawan pada Rumah Sakit XYZ - Lestari, Endang Dwi; Baskoro, Heru (IAI Nasional Laa Roiba Bogor, 2024)
Employee work time discipline has a vital role in maintaining operational efficiency and service quality in hospitals. This research aims to conduct an in-depth analysis of employee working time discipline at XYZ Hospital. Qualitative research methods were used to collect data through in-depth interviews with employees from various divisions in the hospital. The qualitative data was then analyzed thematically to identify patterns, themes and conclusions related to work time discipline. Data analysis was carried out to identify factors that influence work time discipline and their impact on operational efficiency and service quality. It is hoped that the findings of this research will provide valuable insights for hospital management in improving employee working time management and improving operational efficiency. This research contributes to a deeper understanding of employee working time discipline in hospitals, as well as providing a basis for the development of more effective strategies for working time management in healthcare environments.